MEDIA PEMBELAJARAN BERBASIS PERMAINAN MONOPOLI MENINGKATKAN KETERLIBATAN SISWA DALAM PENDIDIKAN AGAMA KATOLIK - Anggraini, Patresia Dita; Permana, Natalis Sukma (Lembaga Penelitian STKIP Widya Yuwana, 2024)
This study aims to find out that Catholic Religious Education learning can use learning media and find out that learning media can use Catholic monopoly games. The background of writing this study is due to the lack of use of learning media in the learning process of Catholicism amid the many learning media used in learning materials other than Catholicism. In addition, because there are still many teachers who teach with the lecture method so that learning becomes saturated and boring. This research uses research and development (R&D) methods and uses the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). Data conducted by researchers in the form of observations, interviews, and questionnaires. The target of the study was a grade V student of SDK Santo Bavo Madiun. The results showed that the assessment of material experts, media experts, as well as positive responses from students during field trials, it can be concluded that this Catholic monopoly game media is